2008
DOI: 10.1111/j.1365-2702.2007.02034.x
|View full text |Cite
|
Sign up to set email alerts
|

Can venous and arterial leg ulcers be differentiated by the characteristics of the pain they produce?

Abstract: Patients' descriptions of pain have the potential to supplement other methods of differentiating between types of leg ulcer and provide an early-warning indicator for transition from venous to arterial ulceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 39 publications
1
18
0
1
Order By: Relevance
“…Some studies reported pain intensity in a way that made it improper to include the data in the meta-analysis. Most of these excluded studies reported pain intensity corresponding to mild to moderate, 40,63 which is similar to results found in the studies included in the meta-analysis. Note that one excluded study 41 report a high prevalence (40%) of intense pain.…”
Section: Other Pain Characteristicssupporting
confidence: 76%
“…Some studies reported pain intensity in a way that made it improper to include the data in the meta-analysis. Most of these excluded studies reported pain intensity corresponding to mild to moderate, 40,63 which is similar to results found in the studies included in the meta-analysis. Note that one excluded study 41 report a high prevalence (40%) of intense pain.…”
Section: Other Pain Characteristicssupporting
confidence: 76%
“…In a previous study, "throbbing", "burning", "itchy", "stinging", and "tender" were extracted as specific sensory pain descriptions for VLU, and our result is consistent with that study. 31 This suggested that SF-MPQ was valid for expressing the pain of VLU in the present study.…”
mentioning
confidence: 67%
“…Other studies of patients with leg wounds reported that individuals used terms to describe their bodily pain similar to terms used to describe venous ulcers, such as throbbing, burning, sharp, sore, aching, stabbing, and itchy. [44][45][46] Persons with wounds also achieved a higher percentage of pain relief than those without leg ulcers. Treatment of the leg ulcer pain may also have helped to alleviate other bodily pain.…”
Section: ■ Discussionmentioning
confidence: 96%